The North American Consortium for Entrepreneurship: Lessons Learned and Best Practices on Hosting International Students - Stella Sixing Xu; Gary B. Roberts; Dorothy Brawley; Bob Desman; Kamal Fatehi (Journal of Global Initiatives, 2010)
In 2004, Kennesaw State University became a part of the North American Consortium for Entrepreneurship (NACE). Its mission is to advance the study and practice of entrepreneurship in the North American business community and develop successful entrepreneurial careers in the expanding markets fostered by the implementation of the North American Free Trade Association (NAFTA). In spring 2006, KSU hosted students from Canada, Mexico, and the United States as part of the NACE global initiative. Volunteers from an on-campus student organization, Students in Free Enterprise (SIFE), coordinated the project. This paper presents a descriptive case study of the semester-long exchange, along with a discussion of lessons learned and some suggested best practices for similar events.